Vibrational analysis of excited and ground electronic states of all-transretinal protonated Schiff-bases - Kraack, Jan Philip; Buckup, Tiago; Motzkus, Marcus (Physical chemistry, chemical physics, 2011)
We report on vibrational coherence dynamics in excited and ground electronic states of all-transretinal protonated Schiff-bases (RPSB), investigated by time-resolved Degenerate Four-Wave-Mixing (DFWM). The results show that wave packet dynamics in the excited state of RPSB consist of only low-frequency (<800 cm−1) modes. Such low-frequency wave packet motion is observed over a broad range of detection wavelengths ranging from excited state absorption (∼500 nm) to stimulated emission (>600 nm). Our results indicate that low-frequency coherences in the excited state are not activated directly by laser excitation but rather by internal vibrational energy redistribution. This is supported by the observation that similar coherence dynamics are not observed in the electronic ground state. Challenging previous experimental results, we show that the formation of low-frequency coherence dynamics in RPSB does not require significant excess vibrational energy deposition in the excited state vibrational manifolds. Concerning ground state wave packet dynamics, we observe a set of high-frequency (>800 cm−1) modes, reflecting mainly single and double bond stretching motion in the retinal polyene-chain. Dephasing of these high-frequency coherences is mode-dependent and partially differs from analogous vibrational dephasing of the all-transretinal chromophore in a protein environment (bacteriorhodopsin).
Gesehen am 08.07.2022